Applying EDON Methodology and SBVR2OWL Mappings for Building an Ontology-Aware Software - Gaspoz, Cecilia (2013)
In Ontology-Aware Software, ontologies are use at run time to, for example, use their content in operations of information searching or as database substitutes for information storage. In order to integrate the software development and ontology building processes, involved in building ontologyaware information system a methodology called EDONhave defined. The main disadvantage of this methodology is that the heuristic to generate an implemented ontology from the requirement elicitation is not complete enough. On the other hand, recently, the Object Management Group (OMG) has standardized a language called Semantics of Business Vocabulary and Rules (SBVR) and different approaches have been proposed to map SBVR expressions into the OWL ontology language. In this paper, we report our experience in developing an ontology-aware information system by using an adaptation of the EDON methodology including the SBVR2OWL mappings.